Water Resources Assessment and Management in Drylands (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Drylands are fragile environments and, therefore, highly susceptible to environmental changes. They cover nearly 50% of the world’s land surface and are increasingly being reclaimed by a growing population for food production and urbanization. This makes water resources management in drylands an extremely important issue. The unplanned water resources development may result in aquifer depletion, soil and/or water salinization, loss of water through evapotranspiration due to inadequate irrigation systems, and land degradation (e.g., soil erosion, soil crusting, and sand encroachment).